Рейтинг адміністративних районів Волинської області за природно-географічними показниками і станом довкілля - Краснопольська, Надія Володимирівна; Ільїна, Мар'яна; Krasnopolska, Nadiia V.; Ilina, Mariana (Сумський державний педагогічний університет імені А. С. Макаренка, 2015)
На основі фондових джерел економіко-географів обраховано та розроблено рейтинговий список та групування адміністративних районів Волинської області за забезпеченістю природно-ресурсним потенціалом і продуктивністю його використання.

On the basis of the stock springs economic-geographers calculated and designed rating list and grouping of the administrative districts of Volyn region on the availability of natural-resource potential and performance (efficiency) of its use. The analysis and the relationship of these groups of indicators in the region.The expediency of their consideration and impact on the main macroeconomic indicators of socio-economic development, in particular the performance of agriculture. Identifies three levels of development of the agricultural sector by districts. Investigated the environmental condition of Volyn region, revealed spatial differences and held the ranking and grouping areas according to the main indicators of ecological condition.
Rating of Administrative Districts of Volyn Region According to the Natural Geographical Indicators and State of the Environment
Keywords: рейтинг; природно-географічні показники; адміністративні райони; природно-ресурсний потенціал